Pelvic reconstruction following resection of malignant bone tumours using a stemmed acetabular pedestal cup. (June 2017) - Hipfl, C.; Stihsen, C.; Puchner, S. E.; Kaider, A.; Dominkus, M.; Funovics, P. T.; Windhager, R.
Abstract : Aims: Pelvic reconstruction after the resection of a tumour around the acetabulum is a challenging procedure due to the complex anatomy and biomechanics. Several pelvic endoprostheses have been introduced, but the rates of complication remain high. Our aim was to review the use of a stemmed acetabular pedestal cup in the management of these patients. Patients and Methods: The study involved 48 patients who underwent periacetabular reconstruction using a stemmed pedestal cup (Schoellner cup; Zimmer Biomet Inc., Warsaw, Indiana) between 2000 and 2013. The indications for treatment included a primary bone tumour in 27 patients and metastatic disease in 21 patients. The mean age of the patients at the time of surgery was 52 years (16 to 83). Results: At a median follow-up of 6.6 years (95% confidence interval 4.6 to 8.2), local control was achieved in all patients; 19 patients had died (16 of disease). Complications occurred in 19 patients (40%), of which deep infection was the most common, affecting eight patients (17%). Seven patients (15%) had a dislocation of the hip. Aseptic loosening was found in three patients (6%). Two (4%) underwent hindquarter amputation for non-oncological reasons. The risk of revision, with death being treated as a competing event, was 28% at one year, 39% at five years and 48% at ten years post-operatively. The mean Musculoskeletal Tumour Society Score at final follow-up was 71% (27% to 93%). Conclusion: This type of reconstruction is a satisfactory option for the treatment of patients with a periacetabular tumour. There remains, however, a high rate of complication, which may be reduced by future modifications of the device such as silver coating and tripolar articulation. Cite this article: Bone Joint J 2017;99-B:841–8.